Dynamics of data flows on the low-activated vanadium alloy for thermonuclear power engineering (analysis of four international data bases) - Shepelev, A.G.; Kurilo, Yu.P.; Krivchenko, O.V. (Вопросы атомной науки и техники, 2015)
The paper presents the results of scientometric analysis of data flows in the International Data Bases SCOPUS, INSPEC, INIS, MSCI over a period since 1971 to 2014 on low-activated vanadium alloys suitable for operation as structural materials under extremely hard conditions in the future fusion reactors. The data on the dynamics of publications and contributions in them from the scientists of different countries have been obtained. The types and languages of publications have been identified. The analysis shows that investigations on the low-activated vanadium alloys are of current importance. Представлены результаты наукометрического анализа информационных потоков за 1971-2014 гг. в Международных базах данных SCOPUS, INSPEC, INIS, MSCI по малоактивируемым сплавам ванадия, пригодным в качестве конструкционных материалов для работы в очень тяжелых условиях термоядерных реакторов будущего. Получены данные о динамике публикаций, вкладе в них ученых различных стран, выяснены типы и языки публикаций. Анализ показал, что исследования по малоактивируемым сплавам ванадия являются актуальными. Представлено результати наукометричного аналізу інформаційних потоків за 1971-2014 рр. у Міжнародних базах даних SCOPUS, INSPEC, INIS, MSCI з малоактивованих сплавів ванадію, придатних в якості конструкційних матеріалів для роботи в дуже важких умовах термоядерних реакторів майбутнього. Отримано дані про динаміку публікацій, внесок в них вчених різних країн, з'ясовані типи і мови публікацій. Аналіз показав, що дослідження з малоактивованих сплавів ванадію є актуальними.